High fat diet induced obesity is mitigated in Cyp3a-null female mice. (1st June 2018) - Kumar, Ramiya; Litoff, Elizabeth J.; Boswell, W. Tyler; Baldwin, William S.
Abstract: Recent studies indicate a role for the constitutive androstane receptor (CAR), pregnane X-receptor (PXR), and hepatic xenobiotic detoxifying CYPs in fatty liver disease or obesity. Therefore, we examined whether Cyp3a-null mice show increased obesity and fatty liver disease following 8-weeks of exposure to a 60% high-fat diet (HFD). Surprisingly, HFD-fed Cyp3a-null females fed a HFD gained 50% less weight than wild-type (WT; B6) females fed a HFD. In contrast, Cyp3a-null males gained more weight than WT males, primarily during the first few weeks of HFD-treatment. Cyp3a-null females also recovered faster than WT females from a glucose tolerance test; males showed no difference in glucose tolerance between the groups. Serum concentrations of the anti-obesity hormone, adiponectin are 60% higher and β-hydroxybutyrate levels are nearly 50% lower in Cyp3a-null females than WT females, in agreement with reduced weight gain, faster glucose response, and reduced ketogenesis. In contrast, Cyp3a-null males have higher liver triglyceride concentrations and lipidomic analysis indicates an increase in phosphatidylinositol, phosphatidylserine and sphingomyelin. None of these changes were observed in females. Last, Pxr, Cyp2b, and IL-6 expression increased in Cyp3a-null females following HFD-treatment. Cyp2b and Fatp1 increased, while Pxr, Cpt1a, Srebp1 and Fasn decreased in Cyp3a-null males following a HFD, indicating compensatory biochemical responses in male (and to a lesser extent) female mice fed a HFD. In conclusion, lack of Cyp3a has a positive effect on acclimation to a HFD in females as it improves weight gain, glucose response and ketosis. Graphical abstract: Highlights: Cyp3a-null female mice are resistant to the effects of a high-fat diet. Cyp3a-null females show improved metabolic responses, including glucose tolerance. In contrast, Cyp3a-null male mice show increased liver triglycerides. Gene expression changes indicate decreased lipid metabolism and increased uptake.